2013
DOI: 10.1016/j.bbi.2012.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-induced anorexia in tumor-bearing mice is dependent on cyclooxygenase-1

Abstract: , Cancer-induced anorexia in tumor-bearing mice is dependent on cyclooxygenase-1, 2013, Brain, behavior, and immunity, (29) AbstractIt is well-established that prostaglandins (PGs) affect tumorigenesis, and evidence indicates that PGs also are important for the reduced food intake and body weight loss, the anorexiacachexia syndrome, in malignant cancer. However, the identity of the PGs and the PG producing cyclooxygenase (COX) species responsible for cancer anorexia-cachexia is unknown. Here, we addressed thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 59 publications
2
26
0
Order By: Relevance
“…Those known to overlap with the hypothesized mechanisms underlying cytokine-induced affective, somatic and cognitive behavior involve: iNOS and COX enzymatic activities, neuronal death, and tryptophan metabolism. Briefly, the negative behavioral consequences of tumors are associated with elevations in iNOS expression among various hypothalamic regions (Wang et al, 2001; Yang et al, 2012) and elevations in cerebral blood vessel expression of COX-1 (Ruud et al, 2013; not COX-2 (Wang et al, 2001). The results from measuring constitutive hippocampal COX-2 expression in tumor-bearing models with affective-like behavior or cognitive impairment are mixed (Yang et al, 2012, 2014).…”
Section: Rodent Models Of Cancermentioning
confidence: 99%
“…Those known to overlap with the hypothesized mechanisms underlying cytokine-induced affective, somatic and cognitive behavior involve: iNOS and COX enzymatic activities, neuronal death, and tryptophan metabolism. Briefly, the negative behavioral consequences of tumors are associated with elevations in iNOS expression among various hypothalamic regions (Wang et al, 2001; Yang et al, 2012) and elevations in cerebral blood vessel expression of COX-1 (Ruud et al, 2013; not COX-2 (Wang et al, 2001). The results from measuring constitutive hippocampal COX-2 expression in tumor-bearing models with affective-like behavior or cognitive impairment are mixed (Yang et al, 2012, 2014).…”
Section: Rodent Models Of Cancermentioning
confidence: 99%
“…EP4 is well represented in the hypothalamic and brain stem structures regulating feeding behavior (Williams and Elmquist, 2012;Zhang and Rivest, 1999) and an anorexic response was obtained when PGE2 was injected intraventricular (V3) or intra-PVN (Skibicka et al, 2011). However, contrasting results are seen in a tumor model for anorexia-cachexia where neither the neuronal EP4 nor global mPGES-1 deletions could rescue the tumor-induced appetite loss (Ruud et al, 2013a).…”
Section: Anorexiamentioning
confidence: 88%
“…Inflammation-induced PGE2 was shown to be critical for the fever response (Engblom et al, 2003), but PGE2 was also shown to be one of several mediators contributing to the HPA-axis activation (Elander et al, 2009;Morimoto et al, 1989a), aversive behavioral changes (Fritz, 2012), hyperalgesia (Ferreira, 1972;Ferreira et al, 1973;Kamei et al, 2004;Trebino et al, 2003), and wakefulness (Huang et al, 2003).. However, it was found to have only a limited role in the anorectic response (Elander et al, 2007;Ruud et al, 2013a).…”
Section: The Bbb As An Interface For Immune Signal-transductionmentioning
confidence: 99%
“…It is also well established that inflammatory signalling and inflammatory-induced prostaglandins have a central role in tumorigenesis and have been proposed as key mediators of cancer anorexia (Gelin et al , 1991, Ruud et al , 2013a). The biological function of prostaglandin E 2 (PGE 2 ) is mediated via four G-protein-coupled receptors EP 1 –EP 4 (Sugimoto and Narumiya, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggest a multifactorial nature of the anorexia-cachexia syndrome with deregulation of several physiological and biochemical systems (Tisdale, 2009). For example, in a murine cancer model (MCG 101), the role of innate immune signalling mediated by myeloid cells has been demonstrated for the development of anorexia (Ruud et al , 2013b), as well as the involvement of prostaglandins particularly those derived from cyclooxygenase-1 (Ruud et al , 2013a). Changes in expression of guanine nucleotide-binding proteins, which are involved in G-protein-coupled receptor signalling, have been shown in adipocytes of mice bearing MAC16 tumours as well as in a patient with cancer-associated weight loss (Islam-Ali et al , 2001).…”
mentioning
confidence: 99%